2016
DOI: 10.1055/s-0035-1562621
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,4′-Disubstituted and Spiro-tetrahydroquinolines via Photochemical Cyclization of Acrylanilides and the First Synthesis of (±)-trans-Vabicaserin

Abstract: The synthesis of vabicaserin analogues bearing a quaternary center or spiro substitution at the 4-position has been studied via a [6π]-acrylanilide cyclization employing flow photochemistry in a mesoscale and microfluidic flow photoreactor. The method is also used to synthesize 4,4′-disubstituted tetrahydroquinolines and, furthermore, enables the first synthesis of (±)-trans-vabicaserin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Koolman and co-workers showed that, when an acetone solution of the acrylanilide derivative 276 was subjected to a photochemical [6π]-cyclization by treatment with quartz-glassfiltered UV light from a mercury middle-pressure lamp in a mesoscale tube-based flow reactor, the fused dihydroquinolinones 277 were obtained in good yields (Scheme 66). 163 These compounds were further reduced with borane−THF and treated with trifluoroacetic acid to remove the Boc protection to furnish (±)-trans-vabicaserin and related 4,4′-disubstituted tetrahydroquinolines 278 in excellent yields. The photochemical step was shown to tolerate well the presence of substituents on the aromatic ring, as well as on the acrylic moiety.…”
Section: Formation Of the N−c 2 Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Koolman and co-workers showed that, when an acetone solution of the acrylanilide derivative 276 was subjected to a photochemical [6π]-cyclization by treatment with quartz-glassfiltered UV light from a mercury middle-pressure lamp in a mesoscale tube-based flow reactor, the fused dihydroquinolinones 277 were obtained in good yields (Scheme 66). 163 These compounds were further reduced with borane−THF and treated with trifluoroacetic acid to remove the Boc protection to furnish (±)-trans-vabicaserin and related 4,4′-disubstituted tetrahydroquinolines 278 in excellent yields. The photochemical step was shown to tolerate well the presence of substituents on the aromatic ring, as well as on the acrylic moiety.…”
Section: Formation Of the N−c 2 Bondmentioning
confidence: 99%
“…Koolman and co-workers performed a direct synthesis of spirocyclic substituted 4,4′-cyclobutyl tetrahydroquinolines 289 in a microfluidic flow photoreactor via a [6π] cyclization of an acrylanilide precursor 288 (Scheme 72). 163 A regio-and diastereoselective synthesis of bridged benzothiaoxazepine-1,1-dioxides containing an embedded tetrahydroquinoline unit was achieved in three steps from readily available starting materials (Scheme 73). 170 The starting N-aryl-2-fluorobenzenesulfonamides were alkylated with trans-2,3-epoxycinnamyl alcohol-derived tosylates in the presence of K 2 CO 3 in DMF at 60 °C to give the N-alkyl sulfonamides 290, which underwent an intramolecular epoxide ring-opening in the presence of p-toluenesulfonic acid in toluene at 80 °C to form trans-4-aryl-3-hydroxytetrahydroquinoline derivatives 291.…”
Section: Formation Of the N−c 2 Bondmentioning
confidence: 99%
“…Photochemical cyclizations are historical transformations that are once again gaining utility due to improved reactivity in flow. For instance, at AbbVie a photochemical cyclization was carried out on gram scale, providing a key intermediate 65 for a 5HT 2C program (Scheme A) . Similarly, tricyclic scaffolds have been prepared by [2 + 2] photocycloaddition using a continuous flow setup .…”
Section: Flow Chemistry Methodology: Flow Over Batchmentioning
confidence: 99%
“…This endoperoxide 63 was prepared by the introduction of dihydroartemisinic acid 64, oxygen gas, and photosensitizer to 40A). 90 Similarly, tricyclic scaffolds have been prepared by [2 + 2] photocycloaddition using a continuous flow setup. 91 Small scale runs were transitioned to a large-scale flow photoreactor, where 10−20 g of starting material could be processed in a 9.5− 14.6 h period, with isolated yields similar to the small scale runs (Scheme 40B).…”
Section: Flow Chemistry Applications Across the Pharmaceutical Industrymentioning
confidence: 99%
“…Koolman and co-workers carried out the synthesis of vabicaserin analogues by photocyclization reaction using a mesoscale and microfluidic flow photoreactor. 59 Vabicaserin is a polycyclic system with a 1,2,3,4-tetrahydroquinoline core, which has been clinically investigated as a 5-HT 2C agonist for the treatment of schizophrenia. 60 Furthermore, 1,2,3,4tetrahydroquinoline is the substructure of many biologically active compounds and natural products as a consequence.…”
Section: Organic Process Research and Developmentmentioning
confidence: 99%